2020
DOI: 10.3390/chemosensors8010015
|View full text |Cite
|
Sign up to set email alerts
|

Silver Chloride/Ferricyanide-Based Quasi-Reference Electrode for Potentiometric Sensing Applications

Abstract: Processes’ occurring at the Ag/AgCl/Cl–, ([Fe(CN)6]3–/4–) ions interface study results are presented. Conditions are selected for the mixed salts’ precipitate formation on the silver surface. It has been shown that the potential of a silver screen-printed electrode (AgSPE) coated with a mixed precipitate containing silver chloride/ferricyanide is stable in the presence of [Fe(CN)6]3–/4–. The electrode can serve as a quasi-reference electrode (QRE) in electrochemical measurements in media containing ions [Fe(CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 59 publications
(81 reference statements)
0
18
0
Order By: Relevance
“…Standard silver chloride electrodes are used as the reference electrodes for the analysis of liquids, and single-use standard skin medical electrodes for electrocardiography [34] or (in later studies) silver/chloride electrodes [9] manufactured from conductive silver paste PP-17C from RPE Delta-Pastes Ltd. (Russia), which is placed on a nonconductive substrate using screen printing technology, were used for non-invasive (skin) analysis. The problem of the instability of these electrodes' potential in the presence of mediator system was solved by modifying the surface of such electrodes with a mixed precipitate of chloride and silver ferricyanide [9].…”
Section: Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Standard silver chloride electrodes are used as the reference electrodes for the analysis of liquids, and single-use standard skin medical electrodes for electrocardiography [34] or (in later studies) silver/chloride electrodes [9] manufactured from conductive silver paste PP-17C from RPE Delta-Pastes Ltd. (Russia), which is placed on a nonconductive substrate using screen printing technology, were used for non-invasive (skin) analysis. The problem of the instability of these electrodes' potential in the presence of mediator system was solved by modifying the surface of such electrodes with a mixed precipitate of chloride and silver ferricyanide [9].…”
Section: Sensorsmentioning
confidence: 99%
“…The potentiometric method, where a mediator system is used for generating the signal-forming substances, was suggested earlier [3][4][5], for the estimating of OS considering the integral antioxidant activity (AOA) as its criterion. Later, taking into account that analytical signal generated by two different processes occurring simultaneously or successively, authors [6][7][8][9] introduced the term "a hybrid variant of potentiometric method" to emphasize the difference from the conventional potentiometric measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The geometric area of the working area of one electrode was 6-9 mm 2 (3 × 2-3 mm). Modification of the silver electrode included the electrodeposition of a SCSF on the working surface, according to the technique described in [44]. For that purpose, the silver electrode was inserted in a continuously stirred buffer solution pH 5 (see Table S3 in Supplementary Materials) that contained 1 mM K 3 [Fe(CN) 6 ] and 0.05 mM K 4 [Fe(CN) 6 ], and then, it was polarized at a constant potential of 0.325 V (vs. Ag/AgCl/KCl, 3.5 M) for 120 s. The resulting electrode was labeled SCSF/Ag/PET and used as a reference FFE in a potentiometric sensor system.…”
Section: Ffes Manufacturingmentioning
confidence: 99%
“…Due to the registration of a mixed potential, the AuNPs/CV/PET demonstrates a worse potential stability than the CV/PET. The characteristics of the electrode that differ from the SCSF/Ag/PET by the non-conductive substrate (alumina ceramics), by SEM, were described in [44]. It was shown that small Ag 3 [Fe(CN) 6 ] crystals fill the pores between large AgCl crystals, which leads to a greater stability of the potential of the electrode with a mixed precipitate (Ag 3 [Fe(CN) 6 ] + AgCl) as compared with a silver chloride electrode (AgCl only) in a medium (solution, membrane) containing [Fe(CN) 6 ] 3-/4-.…”
Section: Ffes Studymentioning
confidence: 99%